2012
DOI: 10.1121/1.4756951
|View full text |Cite
|
Sign up to set email alerts
|

Narrow sidebranch arrays for low frequency duct noise control

Abstract: The present study investigates the sound transmission loss across a section of an infinitely long duct where one or more narrow sidebranch tubes are installed flushed with the duct wall. The finite-element method is used to compute the wave propagation characteristics, and a simplified theoretical analysis is carried out at the same time to explain the wave mechanism at frequencies of high sound reduction. Results show that the high sound transmission loss at a particular frequency is due to the concerted acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…4). Figures 3 and 4 thus show that unlike the case of closely packed side-branch tubes, 9 the individual TL peaks are caused by resonances of individual tubes and not by concerted interplay among several tubes. Figure 5 shows the comparison of TL of the abovedescribed optimized silencer (black line) with two nonoptimized silencers with the same number of side-branch tubes.…”
Section: Numerical Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…4). Figures 3 and 4 thus show that unlike the case of closely packed side-branch tubes, 9 the individual TL peaks are caused by resonances of individual tubes and not by concerted interplay among several tubes. Figure 5 shows the comparison of TL of the abovedescribed optimized silencer (black line) with two nonoptimized silencers with the same number of side-branch tubes.…”
Section: Numerical Resultsmentioning
confidence: 83%
“…It is also assumed that the waveguide downstream the silencer is infinite (or anechoic), so that there is no wave impinging from the right side. Within this work, as it has been adopted in the previous works, [3][4][5][6][7][8][9][10][11] the fluid is considered non-dissipative (all forms of acoustic energy dissipation are neglected), and stationary. Even if in almost all practical applications the fluid would be moving, the assumption of stationary fluid does not represent too much simplification, as Tang and Li 12 have reported that slow in-duct airflow does not affect the transmission loss of single or double sidebranch arrangements very much.…”
Section: Introductionmentioning
confidence: 99%
“…These tubes act as quarter wavelength resonators, which are able to stop the sound transmission by concerted resonance [33]. In his experiment, Field found that the weighted sound reduction index of his proposed device was around 22 dB.…”
Section: Resonant Devicesmentioning
confidence: 99%
“…For the coupling between sub-chambers, it has been shown that an array of Helmholtz resonators [20] or cavity resonators [21,22] can provide a wider TL with each resonator contributing a distinct peak. This has also been validated experimentally through the design of exhaust stack silencers [23].…”
Section: Introductionmentioning
confidence: 99%